A novel vaccine designing approach through analyzing computational tools against pathogenic vibrio cholerae’s outer membrane protein of O1 strain as adjuvant - Hossain, Ashraf (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2022.